Massive growth of paratesticular myxoid liposarcoma recurrence and inguinal metastases following scrotal violation: A case report - Oskar, Deddy; Qosasi, Kiagus FF. (Journal of Neonatal Surgery, 2025)
Paratesticular myxoid liposarcomas are exceedingly uncommon soft tissue tumor, comprising merely 3.3% of all liposarcomas in paratesticle. The primary treatment involves total surgical removal with orchiectomy performed through an inguinal incision. Even though radical orchiectomy is still the best treatment to date, recurrence is still inevitable. There is possibility of tumor recurrence and metastasis due to scrotal violation. Trans-scrotal approach of orchiectomy increased the possibility of local recurrence and possible spread by allowing the cancerous cells to leak into the adjacent tissues. We discuss the clinical presentation of the case, the therapeutic management, and the possible complications after scrotal violation of prior removal surgery. We report a case of a 69-year-old man with painful recurrent scrotal tumor along with massive growth and spread to the spermatic cord and inguinal region after right orchiectomy with trans scrotal approach one year earlier. The tumors were 23 x 25 x 8 cm for the inguinal tumor, 13 x 9 x 7 cm with ulcerative surface for the scrotal tumor, and 12 x 6.5 x 5 cm for the spermatic cord tumor. Our patient then had wide excision tumor surgery with a radical lymphadenectomy. Similar cases of recurrent paratesticular myxoid liposarcoma have been reported; however, the recurrence occurred over a year and no metastases had been found. In our case, the recurrent tumor had significant development rapidly within a year after scrotal violation and was also found to have already metastasized to the inguinal region. Massive recurrence tumor growth and spread in paratesticular liposarcoma following orchiectomy is rarely heard of. Surgical treatment is still the preferred treatment to date, but local recurrence and metastasise somehow is inevitable. Tumor recurrence and spread hopefully can be prevented by proper diagnosis and surgical management of the tumors; high ligation of the cord, inguinal approach and ensure negative margin of tumors. This case report also highlights the significance of avoiding scrotal violations to prevent tumor seeding to adjacent sites, thereby reducing patient morbidity and mortality